PENGEMBANGAN BAHAN AJAR FLASHCARD BERBASIS CANVA UNTUK MENINGKATKAN KETERAMPILAN MEMBACA BAB 3 PENGOBAR SEMANGAT - Syailen Apriandini, Putri; Rostikawati, Teti; Wijaya, Ade (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research applies the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. A total of 37 class III students were designated as test subjects to develop and evaluate the effectiveness of the designed teaching materials. Validation of teaching materials was carried out by three experts, namely media experts, linguists, material experts, with media expert validation results of 90.66%, linguist validation results of 94.66%, material validation results of 94% with average results The 92.66% included in the "Very Eligible" criteria is strengthened by the N-Gain score reaching 0.83, in the "High" category. Likewise, with the questionnaire results, the teacher's response was 100% and the trial results showed an average score of 98.3% of the students. From these results, it can be concluded that flashcard teaching materials prepared using the Canva application are very effective and practical to use in the learning process, and are able to increase student involvement and understanding.